Lawn mower magic - Jonell, Lynne (Magical mix-ups, 2012)
When Derek Willow is invited to visit a friend in the old neighborhood, he and his siblings Abner, Tate, and Celia try to earn money for his train ticket using an enchanted, and very hungry, lawnmower.